THE ROLE OF MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) IN SUPPORTING THE INDONESIAN ECONOMY - Salsabillah, Winda; Hafizzallutfi; Uut Tarissyaa; Nur Azizah; Thia Fathona; Muhammad Raihan (CV. Era Digital Nusantara, 2023)
Indonesia's economy has great potential to achieve sustainable and inclusive growth. In this context, Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting the country's economy. This paper aims to analyze the role of MSMEs in supporting the Indonesian economy and how strengthening the MSME sector can have a positive impact on economic growth, job creation, and reducing economic disparities in the country.